With great difficulty because the given terms do not include an equality sign and not knowing the plus or minus values of many of the terms.
if you do the same action to the top and bottom of a fraction it is equivalent. 4/7 = 8/14 = 12/21 x2 x3 etc.
4n - 7n = 21(4-7) n =21-3n = 21divide both sides by -3n = -7
Since that isn't an equation, there is really nothing to solve.
(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)
3m-5 = 7-21 3m = 7-21+5 3m = -9 m = -3
if you do the same action to the top and bottom of a fraction it is equivalent. 4/7 = 8/14 = 12/21 x2 x3 etc.
how to solve 7 + p = p +7
4n - 7n = 21(4-7) n =21-3n = 21divide both sides by -3n = -7
-3
X3xX4=X3+4=X7 this is the correct answer.
Since that isn't an equation, there is really nothing to solve.
x = 7 7-4/3 x 7 = 1/7 3/21 = 1/7
21/47 - 1/2 - 1 1/4:= 7 - 1/2 - 5/4= (28- 2- 5)/4= 21/4
(4+3)3 → Using order of operations, solve the bracket first. (7)3 → Multiply 21
(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)
2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7
3m-5 = 7-21 3m = 7-21+5 3m = -9 m = -3